Modele selekcji deskryptorów osobowych w badaniach psycholeksykalnych - podejście klasyczne i nierestrykcyjne = The models of personality descriptors selection in psycholexical studies - a classic and nonrestrictive approach - Misiuro, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main purpose of this article is to outline two models of selection of personal descriptors in psycholexical studies: the classic (restrictive) and the nonrestrictive approach. The basic distinguishing feature of both models is the range of word material taken into account during lexical analyzes. In the classic model of analysis, the number of personal descriptors is narrowed down to words that describe only stable dispositions.
Keywords: badania psycholeksykalne; podejście restrykcyjne; podejście nierestrykcyjne; deskryptory osobowe; psycholexical study; restrictive approach; nonrestrictive approach; personality descriptors